2019
DOI: 10.1186/s12876-019-1152-4
|View full text |Cite
|
Sign up to set email alerts
|

“Sarcopenia and intramuscular fat deposition are associated with poor survival in Indonesian patients with hepatocellular carcinoma: a retrospective study”

Abstract: BackgroundA large-scale Japanese study showed that low skeletal muscle index (SMI) and intramuscular fat (IMF) deposition are associated with hepatocellular carcinoma (HCC) survival. Here, we evaluated the effects of SMI and IMF on the survival of Indonesian HCC patients, whose characteristics differ from those of Japanese patients.MethodsSMI and mean muscle attenuation (MA) were evaluated using computed tomography images of the third lumbar vertebra (L3) in a prospective cohort of 100 Indonesian HCC patients.… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
1
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 31 publications
0
23
1
2
Order By: Relevance
“… 6 to stratify patients into those with low and high SMD. In the remaining 17 studies assessing SMD, threshold values used ranged from ≤22.0 HU 23 to ≤44.4 HU 24 , 25 , 26 in male patients and ≤23.5 23 to ≤39.3 24 in female patients. Similar to their analysis of SMI, Aleixo et al reported the proportion of patients with low SMD across multiple thresholds.…”
Section: Resultsmentioning
confidence: 99%
“… 6 to stratify patients into those with low and high SMD. In the remaining 17 studies assessing SMD, threshold values used ranged from ≤22.0 HU 23 to ≤44.4 HU 24 , 25 , 26 in male patients and ≤23.5 23 to ≤39.3 24 in female patients. Similar to their analysis of SMI, Aleixo et al reported the proportion of patients with low SMD across multiple thresholds.…”
Section: Resultsmentioning
confidence: 99%
“…In patients with cirrhosis awaiting liver transplantation (LT), sarcopenia has been shown to be a significant risk factor for waitlist mortality, postoperative complications, and post-LT death 8 10 . Similarly, it has been shown that sarcopenia increases 1-year mortality after surgical resection of hepatocellular carcinoma (HCC) 11 and can predict long-term survival in patients with HCC 12 .…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the moderate risk of bias was determined to be due to study attrition in eight studies, adjustment for other prognostic factors in eight studies, statistical analysis and reporting in five studies. In general, of the 42 included studies, 34 studies were at an overall low risk of bias ( 14 16 , 22 25 , 28 32 , 34 , 35 , 37 , 39 44 , 46 , 47 , 49 59 ), while eight were at an overall moderate risk of bias ( 26 , 27 , 33 , 36 , 38 , 45 , 48 , 60 ).…”
Section: Resultsmentioning
confidence: 99%